Image analysis of volcanic plumes: A simple calibration tool to correct for the effect of wind - Snee, Eveanjelene; Jarvis, Paul Antony; Simionato, Riccardo; Scollo, Simona; Prestifilippo, Michele; Degruyter, Wim; Bonadonna, Costanza (Volcanica, 2023)
Video cameras provide vital information on volcanic plumes from explosive eruptions, such as plume height, for monitoring and research. These images must be calibrated to get accurate quantitative data. However, the presence of wind complicates any calibration as the plume may no longer lie in the image plane, i.e. a plane perpendicular to the camera’s line-of-sight. Here, we present a simple new tool to correct for the effect of wind on the position and height of a volcanic plume as determined from imagery by rotating the image plane to be in the direction of the wind. We show the importance of accounting for the effect of wind on the maximum plume height determined from videos for two case-studies; a Vulcanian explosion from Sabancaya volcano, Peru, and a sustained plume from Mount Etna, Italy. This tool can improve the accuracy of quantitative information extracted from images of volcanic plumes, and should prove useful for both research and monitoring purposes.